REORIENTASI PENDIDIKAN ISLAM DI ERA REVOLUSI INDUSTRI 4.0 - M Samkhan M (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2019)
The implementation of Islamic education is still oriented towards the romanticism of the past rather than looking at the future. The main challenges in the industrial era 4.0 include the issue of the quality of teaching resources. Therefore this study wants to answer; the orientation of the educational paradigm as an epistemological framework which underlies the set of ideas or concepts in the implementation of education as well as the actualization and evaluation of education. The effort to transform Islamic education uses an integrated approach between the reasoning of Bayani, Burhani, and Irfani. The hope, the integrated paradigm produces a scientific structure that emphasizes the creation of know-why and know-how competencies, rather than know-what. In this case it is a philosophical form of Islamic education in its axiological and epistemological aspects, so that professional Islamic education can give birth to a generation of knowledgeable knowledge, mastering technology in addition to holding fast to the religion of God.